Paf-Related Ischemic Stroke: Clinical, Radiological and Echocardiographic Findings - ALTINTAS, Ozge; NIFTALIYEV, Elvin; TASAL, Abdurrahman; Asil, TALİP; ASİL, TALIP (My University, 2015)
Introduction: Atrial fibrillation (AF) is the most common etiological factor involved in ischemic stroke. There are no definitive data regarding the prevalence of paroxysmal AF (PAF)-related ischemic stroke. In this study, we prospectively evaluated clinical, radiological and transthoracic echocardiography(TTE) findings and their association with stroke outcomes.